(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Weeds pose a significant challenge in agriculture by competing with crops for essential resources such as water, nutrients, sunlight, and root space, leading to substantial reductions in yield and quality. In addition to their direct competition, weeds serve as alternate and alternative hosts for various pests, including pathogens, insects, mites, nematodes, and rodents, thereby sustaining pest populations and contributing to disease cycles. The relationship between weeds and phytopathogens is complex, with weeds acting as reservoirs and dispersal agents for numerous bacterial, fungal, and viral pathogens. Asymptomatic infection of weeds by pathogens further complicates disease management, making them persistent threats to global food security. Moreover, weeds support a diverse range of insect pests, from monophagous to polyphagous species, which utilize them as food sources, overwintering sites, or breeding grounds. While weeds can exacerbate pest outbreaks, they also play a role in supporting beneficial organisms that contribute to biological control. Given their dual role in agroecosystems, effective weed management is crucial in integrated pest and disease control strategies. Understanding the ecological interactions between weeds, pests, and pathogens is essential for minimizing crop losses while maintaining biodiversity and ecological balance in agricultural landscapes.